In Silico Characterization of Uncharacterized Proteins From Multiple Strains of Clostridium Difficile - Abbasi, Bilal Ahmed; Dharan, Aishwarya; Mishra, Astha; Saraf, Devansh; Ahamad, Irsad; Suravajhala, Prashanth; Valadi, Jayaraman (Frontiers in Genetics, 2022)
Clostridium difficile (C. difficile) is a multi-strain, spore-forming, gram-positive, opportunistic enteropathogen bacteria, majorly associated with nosocomial infections, resulting in severe diarrhoea and colon inflammation. Several antibiotics including penicillin, tetracycline, and clindamycin have been employed to control C. difficile infection, but studies have suggested that injudicious use of antibiotics has led to the development of resistance in C. difficile strains. However, many proteins from its genome are still considered uncharacterized proteins that might serve crucial functions and assist in the biological understanding of the organism. In this study, we aimed to annotate and characterise the six C. difficile strains using in silico approaches. We first analysed the complete genome of six C. difficile strains using standardised approaches and analysed hypothetical proteins (HPs) employing various bioinformatics approaches coalescing, including identifying contigs, coding sequences, phage sequences, CRISPR-Cas9 systems, antimicrobial resistance determination, membrane helices, instability index, secretory nature, conserved domain, and vaccine target properties like comparative homology analysis, allergenicity, antigenicity determination along with structure prediction and binding-site analysis. This study provides crucial supporting information about the functional characterization of the HPs involved in the pathophysiology of the disease. Moreover, this information also aims to assist in mechanisms associated with bacterial pathogenesis and further design candidate inhibitors and bona fide pharmaceutical targets.